Abulcasis Al-Zahrawi, The Surgeon Of Al-Andalus - Cambra, Luisa Maria Arvide (European Scientific Journal, ESJ, 2016)
Among the many scientists who enriched the scientific panorama in medieval Spain, one of the greatest is without any doubt the Cordovan physician and surgeon Abulcasis Al-Zahrawi (circa 936-circa 1013). This paper is an approach to his figure and work, with special reference to his main writing, the Kitab al-Tasrif (Book of the medical arrangement) and analyzes his significance in the history of medicine and surgery.